Exploring Specific miRNA-mRNA Axes With Relationship to Taxanes-Resistance in Breast Cancer - Chen, Danni; Bao, Chang; Zhao, Feng; Yu, Haogang; Zhong, Guansheng; Xu, Liang; Yan, Senxiang (Frontiers in Oncology, 2020)
Breast cancer is the most prevalent type of malignancies in women worldwide. Taxanes (paclitaxel and docetaxel) are widely applied as first-line chemotherapeutic agents, while the therapeutic effect is seriously limited by the development of drug resistance. In the present study, we screened out several miRNAs dysregulated in taxanes-resistant breast cancer samples and confirmed that two miRNAs (miR-335-5p and let-7c-5p) played a major role in cell proliferation, apoptosis and chemo-resistance. In addition, the weighted gene co-expression network analysis (WGCNA) for potential target genes of miR-335-5p and let-7c-5p identified three hub genes (CXCL9, CCR7 and SOCS1) with positive relationship to taxanes-sensitivity. Further, target relationships between miR-335-5p and CXCL9, let-7c-5p and CCR7/SOCS1 were confirmed by dual-luciferase reporter assays. Importantly, the regulatory functions of CXCL9, CCR7 and SOCS1 on proliferation and chemo-resistance were validated. In conclusion, our study shed light on clinical theragnostic relationships between miR-335-5p/CXCL9, let-7c-5p/CCR7/SOCS1 axes and taxanes-resistance in breast cancer.